Philosophy as a Way of Life in Aristotle’s Eudemian Ethics I: A Matter of Life and Death - Fabio Serranito (Eidos. A Journal for Philosophy of Culture)
Despite his inclusion in Hadot’s foundational work on philosophy as a way of life (PWL), Aristotle tends to be sidelined in recent discussions. This is because Aristotelian contemplation is a goal in itself, not clearly associated with a project of transformation of the knower’s practical life. In this article, I use evidence from the Eudemian Ethics (EE) to re-evaluate the relationship between contemplation and practical life by reflecting on the notion of bios (way of life) and the question about the best possible bios. The exploration of the three bioi in EE problematizes the relationship between phronesis and theoria. Furthermore, EE reframes the question of the best possible bios as a thought experiment from an antinatalist stance: for the sake of which would you choose to be born? The result is a reconsideration of Aristotelian contemplation as a matter of vital importance, and as a valid goal within PWL.